Sleepers [videorecording (DVD)] - Bacon, Kevin, 1958-; De Niro, Robert; Hoffman, Dustin, 1937-; Patric, Jason; Pitt, Brad, 1963-; Renfro, Brad, 1982-2008; Driver, Minnie; Levinson, Barry; Levinson, Barry; Carcaterra, Lorenzo (Warner Home Video, 1997)
Sentenced to the Wilkinson School for Boys, four pals are mistreated at will by a cadre of sadistic guards. Fifteen years later, they have an unexpected opportunity for revenge.